Acute oral toxicity and dose-dependent histopathological effects of Indonesian Ciplukan (Physalis angulata L.) extract in Sprague-Dawley rats - Thianti Sylviningrum; Nor Sri Inayati; Setiawati Setiawati; Fitranto Arjadi; Dody Novrial (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
The growing global interest in herbal medicines underscores the importance of safety assessments for traditional plants. Physalis angulata L. (Ciplukan) demonstrates therapeutic potential, yet data on Indonesian extracts remain limited. This study evaluated the acute oral toxicity and determined the median lethal dose (LD50) of Indonesian Ciplukan extract. Twenty-five female Sprague-Dawley rats were divided into five groups (n=5): control (aqueous), and four groups that received extract at 100, 400, 800, or 1200 mg/kg body weight. Over 14 days, researchers monitored clinical signs, body weight, food intake, and organ weights in accordance with Acute Oral Toxicity (OECD Test Guideline 425). Major organs were examined histopathological using the modified International Harmonization of Nomenclature and Diagnostic Criteria. No mortality or significant behavioral changes were observed at any dose. Rats maintained normal body weight gain and food intake. The LD50 was determined to be exceeded 1200 mg/kg, indicating favourable acute safety. However, histopathological analysis revealed significant dose-dependent necrotic changes (p < 0.05) in the lungs, kidneys, liver, and spleen at doses of 400 mg/kg and above. Liver and spleen damage were detected first at this threshold. These findings indicate an LD50 above 1200 mg/kg body weight for Indonesian Ciplukan extract, supporting its acute safety. Nonetheless, subclinical organ toxicity occurred at doses of 400 mg/kg or higher, emphasizing the need for dose optimization in phytomedicine. The study provides regulatory-grade toxicological data to support evidence-based standardization of Indonesian herbal medicines and highlights the necessity for further research on sub chronic and chronic toxicity to establish safe therapeutic doses.